1987
DOI: 10.1103/physrevlett.59.2788
|View full text |Cite
|
Sign up to set email alerts
|

CrO2—A New Half-Metallic Ferromagnet?

Abstract: Spin-resolved photoemission from polycrystalline Cr02 films shows a spin polarization (P) of nearly +100% for binding energies near 2 eV belo~the Fermi level (El. -). Despite the metallic resistivity behavior, extremely low intensity is observed in the photoemission spectra near EF. Our findings are in contrast to recent band-structure calculations, predicting Cr02 to be a half-metallic ferromagnet with I' =+100% at Ep. PACS numbers: 75.50.Cc, 71.25.Pi, 79.60.Cn The ferromagnet Cr02 is one of the technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
169
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(183 citation statements)
references
References 17 publications
11
169
3
Order By: Relevance
“…Together with the shift of the minority spin DOS from the bottom of the conduction band to higher energy, there appears a dip in the majority spin DOS at the Fermi level which can be taken as an indication of the tendency toward a gap formation. The decrease of the DOS at E F in comparison with that obtained in [8] may be partially responsible for the reduced signal close to E F observed in photo-electron spectroscopy [9]. In our calculations, however, CrO 2 is still a metal albeit with the reduced DOS at the Fermi level.…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…Together with the shift of the minority spin DOS from the bottom of the conduction band to higher energy, there appears a dip in the majority spin DOS at the Fermi level which can be taken as an indication of the tendency toward a gap formation. The decrease of the DOS at E F in comparison with that obtained in [8] may be partially responsible for the reduced signal close to E F observed in photo-electron spectroscopy [9]. In our calculations, however, CrO 2 is still a metal albeit with the reduced DOS at the Fermi level.…”
contrasting
confidence: 46%
“…However the magnetic susceptibility in the paramagnetic phase exhibits a Curie-Weiss-like behaviour with a local moment of also 2 µ B indicating that the mechanism for ferromagnetic behaviour is not a band (Stonerlike) mechanism. Local moments indicate strong correlation effects and this was in fact suggested by early photoemission data [9] which looked more like those of a semiconductor with a vanishing density of states (DOS) at the Fermi energy and a spin polarization of nearly 100 % for binding energies about 2 eV below the Fermi level. To resolve this controversy we carried out the calculations in the LSDA+U approach which is superior to LSDA since it can indeed yield a gap if the local Coulomb interactions are large enough.…”
mentioning
confidence: 99%
“…[14] Third, the present system has unique symmetry that ensures its topological character and is composed of two highly industrialized oxides, for which process technologies are rather mature for fabrication of the heterostructure. [20,21] In summary, we demonstrated that the interfacial electrons at the CrO 2 /TiO 2 heterojunction can be fashioned into single-spin Dirac states. In the superlattice model, we can obtain a Chern number = 2 QAH phase, which will enable dissipationless digital signal transmisstion with minimal influence of noise.…”
mentioning
confidence: 74%
“…Bulk CrO 2 (structure shown in Fig. 1) is a robust half metal even at elevated temperatures, [19][20][21] and widely used in enterprisegrade data storage. Here, we consider the possibility to fashion the CrO 2 into single-spin Dirac states by interfacial orbital design.…”
mentioning
confidence: 99%
“…The observed asymmetry implies the existence of spin-polarized currents, which are fully tunable by a proper choice of gate and bias voltages. By increasing the polarization of the ferromagnet, the diode effect could be increased up to a ∆I value of 100% [30]. Such carbon-nanotube spin diodes could easily be positioned using ac-dielectrophoresis [24], and could be operated at room temperature by reducing their size [31].…”
mentioning
confidence: 99%